The Role of Some Iraqi Accounting Rules in Enhancing the Reliability of Accounting Information and Improving Tax Transparency : (Applied Study in Iraqi General Tax Authority) - Hayder Oudah Kadhim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to identify the extent to which economic units apply accounting rules as well as identify similarities or differences between what was applied by them and the requirements of the accounting base and indicate the impact of these differences on the financial statements and then on the financial ratios used in the analysis of these statements to help enhance well as help improve tax transparency. Research applied in Iraqi Tax Authority on 2021, 2022, and 2023, where the Authority's financial statements were analyzed to identify the basic points can be enhanced and tax transparency can be improved. The research reached several conclusions, the most important of which is that the most important of which is to follow the accounting rules for each item comprised in the financial declarations that help companies reduce the disparity that can exist in the treatment of a particular item of the financial statements, and thus increase the confidence of users of the lists with the information they contain and this was evident in the research sample when applying the accounting rules.